Identification and pharmacokinetics of saponins in Rhizoma Anemarrhenae after oral administration to rats by HPLC-Q-TOF/MS and HPLC-MS/MS - Wang Hai-Qiao; Lan Fen; Zhang Yi-Han; Xia Jin-Er; Gong Xiao-Mei; Liu Min (Acta Pharmaceutica)
Rhizoma Anemarrhenae is a well-known herbal medicine with saponins as its commonly regarded major bioactive components. It is essential to classify the properties of saponins which are associated with their toxicity and efficacy. In this study, 25 compounds were identified by HPLC-Q-TOF/MS in the extract of Rhizoma Anemarrhenae and 8 saponins were detected in rat plasma by HPLC-MS/MS after oral administration of this extract. These were neomangiferin, mangiferin, timosaponin E1, timosaponin E, timosaponin B-II, timosaponin B-III, timosaponin A-III and timosaponin A-I. A sensitive and accurate HPLC-MS/MS method was developed and successfully applied to a pharmacokinetic study of the abovementioned eight saponins after oral administration of the Rhizoma Anemarrhenae extract to rats. The method validation, including specificity, linearity, precision, accuracy, recovery, matrix effect and robustness, met the requirements of the intended use. The pharmacokinetic parameter, Tmax value, ranged from 2 to 8 h for these eight saponins whereas their elimination half-life (t1/2) ranged from 4.06 to 9.77 h, indicating slow excretion. The plasma concentrations of these eight saponins were all very low, indicating a relatively low oral bioavailability. All these results provide support for further clinical studies.